(untitled) (UNED Research Journal, 2022)
Introduction: The size of protected areas is often insufficient for viable predator populations, which causes habitats overlap with humans. The resulting conflicts, for example, predation on domestic animals, negatively affect both wildlife and human well-being. Objective: To estimate the economic impact of human-wildlife conflicts in the Alberto Brenes Biological Reserve, Alajuela, Costa Rica. Methods: Between October 2017 and April 2018, we interviewed 59 property managers in and near the reserve’s buffer zone. They were chosen from conflict reports and “snowball” references. Results: Wild animals killed 1 846 domestic animals from 2000 to 2018, with an economic loss of 48 000. The Coyote, Canis latrans, killed 1 074 animals, worth 4 000; equivalent data: felines 261 animals, 21 000; snakes 33 animals (Fer-the-lance, Bothrops asper: 18 000). Veterinary treatment for 28 surviving animals cost 3 000. Conclusion: While the Coyote killed more animals, felines and snakes produced the highest economic cost. Appropriate institutional intervention would reduce the problem.